Injuries, risk factors, and prevention strategies in bicycle motocross (BMX): a scoping review - Rockliff, C.; Pulsifer, K.; Gupta, S.; Jewell, C. B.; Black, A. M. (Sports Health: A Multidisciplinary Approach, 2025)
Context: Bicycle motocross (BMX) has become increasingly popular since its inclusion in the 2008 Olympics, but it has some of the highest injury rates (IRs) in multisport studies. To support planning for tailored primary prevention, understanding gaps in BMX injury prevention is crucial.